Creating ethical organisational cultures through performance management systems in South Africa - Hall, Nicole Lindsay (My University, 2014)
The increase in global and specifically South African, unethical business practices have lead to a focus on the ethical organisational culture and the ethical behaviour of Boards, Directors, management and employees. This study was undertaken to establish the role of performance management systems in the development and maintenance of an ethical organisational culture. The research was based on a qualitative methodology approach and includes ten respondents from organisations within the private and parastatal sectors. The data was analysed using thematic content analysis. The creation of an ethical organisational culture is an integrated process that requires components from the strategic, systems and operational levels of an organisation. Performance management is a key component of the systems level and aims to evaluate employee’s behaviour against set targets and organisational values. The results of the study established two approaches to the inclusion of ethics into the performance management systems, in the form of a ‘tick box’ obligation and ethics as a separate key performance area. The potential of including ethics into the performance management system as an additional way to contribute to the ethical organisation culture has not yet been fully realised. Furthermore, it was established that despite the efforts of organisations to create an ethical culture, the past and present South African Government and external business environment is seen as a barrier to the realisation of ethical interventions.
MBA thesis
Keywords: Organisational culture; Ethical organisations